Surgical Management of Amlodipine Induced Gingival Enlargement - A Case Report - Shrestha, Benju; Lamichhane, Krishna Prasad; Pradhan, Shaili; Gorkhali, Ranjita Shrestha; Koirala, Pramod Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Amlodipine, a calcium channel blocker, used with increasing frequency as antihypertensive and anti-angina drug has been found associated with gingival enlargement. It causes unesthetic appearance and formation of new niches for periodonto-pathogenic bacteria. If severe, it causes difficulty in mastication, speech and oral hygiene maintenance. Its treatment is still largely limited to meticulous oral hygiene maintenance, drug substitution, professional scaling and root planning and surgical excision of enlarged gingival tissue. There are very few reports of amlodipine-induced gingival enlargement at a dose of 5 mg. This case report discusses amlodipine-induced gingival enlargement and its management.